Breathing ‘second life’ into art investigation: Examining the impact of MUVE functionality regarding scale, movement and mood in visual arts - Flannery, Michael (My University, 2020)
Art investigation is an integral part of the world of visual arts. First hand exposure to, and engagement with diverse original works of art in a gallery setting is lauded as an ideal learning scenario. However gallery spaces are not designed for interactivity and most museum walls are designed to be seen, but not touched. Classroom spaces are frequently used for art investigation. However, they are not designed as gallery spaces. They are busy, multi-functional places and investigating secondary sources in a classroom setting is limited in terms of facilitating proximity, multiple vantage points, learner autonomy, interactivity, time and limiting teacher bias. Meaningful art investigation requires prolonged viewing time and guided discovery. Guided discovery entails encouraging viewers to look closely at the work, sharing observations with one another, gradual revelation of information about work, answering and asking questions and eliciting emerging understandings from learners. Secondary sources or copies have always been used in art investigation. However, hard copy and digital reproductions can often mislead learners most especially in relation to actual scale, kinetic movement or mood. Digital copies from Internet searches vary in quality and accuracy. Default digital presentation formats can also deceive. This explorative case study examines the impact of multi-user virtual environment functionality regarding scale, movement and mood in visual arts. Using convergent parallel mixed methods, it evaluates the impact of a specially designed multi-user virtual gallery in Second Life named AISLE (art investigation in a second life environment) in relation to learners’ increased awareness, understating and appreciation of scale, movement and mood related constructs. This study finds that the multi-user virtual gallery AISLE has impacted positively regarding increased awareness and understanding of the more overt and obvious constructs concerning actual scale and movement. The MUVE navigation and camera viewing tools especially aided this progression. However, the study finds that more time and explicit teaching is required to unpack the more covert and complex constructs relating to implied scale, movement and mood. This study will be of particular interest to art teachers who seek an alternative tool to investigate more accurate approximations of the orginal works or those interested in exploring MUVE functionality to extend their traditional classroom approach.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Visual arts; Virtual Gallery; Classroom; Guided discovery; Scale; Movement; Mood